Financial parallelisms England and the United States - Long, Ross (My University, 1899)
Introduction: Science of History; Underlying Forces; Foundation of Civilization; Capital
Citation: Long, Ross. Financial parallelisms England and the United States. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Science of History; Underlying Forces; Foundation of Civilization; Colonization; Theses; Manuscripts (documents)